Plot Scale Nitrogen Balance of Newly Developed Lowland Rice at Kleseleon Village Malaka District, Nusa Tenggara Timur - nFN Sukristiyonubowo; Sugeng Widodo; Kusumo Nugroho (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2017)
Abstract. Study on plot scale nitrogen balance of newly developed lowland rice was conducted in Kleseleon village, Malaka District, Nusa Tenggara Timur in 2014. The soil was classified as ustifluvent with ustic moisture regime. Five treatments were tested including T0: farmers practices, T1: NPKat recommendation rate + Rice straw compost, T2: NPKat recommendation rate + Smart + Rice straw compost, T3: ¾ NPKat recommendation rate + Smart + Rice straw compost and T4: NPKat recommendation rate + Smart + Rice straw compost, in which N, P  and K were split two times. Nitrogen balance was computed according to the differences between nitrogen gains and losses. To quantify total nitrogen input, nitrogen content in urea, dosage of urea, rate of compost, nitrogen concentration in compost, irrigation water supply, and nitrogen concentrations in rain water were collected. Output parameters included rice grains yield, rice straw production, nitrogen concentrations in rice grains and rice straw. The results indicated that surplus nitrogen balances were taken place in all treatments including the farmer practices. Concerning the environmental, agronomical and economic point of views, the recommendation of urea fertilizer rate at least was about 100 kg ha-1 season-1 like done in the farmer practices plus the compost rate about 3000 kg ha-1 season-1. Urea should be available in the district level every planting season was the urea application rate multiplied by total low land area in Malaka district equal to 1.207 tons district -1 season -1.Abstrak. Percobaan neraca hara nitrogen pada skala petak pada sawah bukaan baru dilaksanakan di Dusun Kleseleon, Kabupaten Malaka, Propinsi Nusa Tenggara Timur pada Tahun Anggaran 2014. Tanah yang digunakan termasuk golongan ustifluvent denga kelembaban tanah ustik. Lima teknologi yang menjanjikan diuji pada percobaan ini meliputi T0: Praktek Petani sebagai kontrol, T1: NPKpada dosis  rekomendasi + Kompos jerami, T2: NPKpada dosis  rekomendasi + Smart + Kompos jerami , T3: ¾ NPKpada dosis  rekomendasi rate + Smart + Kompost jerami dan T4: NPKpada dosis rekomendasi + Smart + Kompos jerami, dimana  N, P  dan K diberikan dua kali. Keseimbangan N dihitung berdasarkan berdasarkan selisih antara nitrogen yang masuk ke lahan sawah dengan nitrogen yang hilangdari lahan sawah . Untuk menghitung nitrogen yang masuk ke lahan sawah diperlukan kandungan N pada urea, dosis pupuk urea, kadar nitrogen dalam kompos,  takaran kompos, air irigasi dan kandungan nitrogen pada air irigasi dan air hujan. Sedangkan nitrogen yang hilang dari lahan sawah meliputi hasil gabah dan produksi jerami serta kadar nitrogen pada gabah dan jerami. Hasil penelitian menjukkan bahwa positif nitrogen balance pada semua perlakuan. Mengingat bahaya pencemaran lingkungan, keuntungan agronomik dan ekonomis yang didapat, pemberian Urea sebaiknya dikurangi dari  250 kg ha-1musim-1 menjadi 100 kg Urea kg ha-1musim-1 seperti pada praktek petani dengan memberi kompos jerami sebanyak 3000 kg ha-1musim-1. Dengan demikian urea yanbg harus tersedia di Kabupaten Malaka setiap musim tanam sebanyak dosis urea rekomendasi dikalikan dengan luas sawah di kabupaten Malaka sama dengan  1.207 ton kabupaten -1 musim-1.